ANALISIS REAKSI PASAR ATAS KEBIJAKAN TAX AMNESTY: STUDI PADA BURSA EFEK INDONESIA - Bq. Anggun Hilendri; Eni Indriani; Rento Dewi H (Jurnal Aplikasi Akuntansi, 2017)
Economic events frequently determine stock price fluctuations in stock exchanges. Sometimes, these economic events tend to get negative responses from market participants. This study uses event study analysis, where the event analyzed was the announcement of government policy in the fiscal sector, the tax amnesty. The announcement of the tax amnesty policy implementation is considered to provide information that elicits reaction in the capital market, which can be measured by the abnormal return on the stock before and after the announcement of tax amnesty policy. This event window of this study was 6 trading days i.e. t-3 to t + 3 since tax amnesty policy became published on July 14, 2016. The sample used in this study consisted of 45 companies listed in LQ-45 index during July 2016. Analysis of average abnormal return is performed based on paired sample t test on three days before and three days after the announcement of tax amnesty policy. The test results show that there is a significant difference in market reaction as indicated by abnormal return value. However, the result of abnormal return shows negative value. It means that tax amnesty policy provides negative information for investor, which is contrary to the objective of tax amnesty policy to increase investment.